Managing complex respiratory patients in the community: an evaluation of a pilot integrated respiratory care service. Issue 1 (5th December 2016) - Gillett, K; Lippiett, K; Astles, C; Longstaff, J; Orlando, R; Lin, S X; Powell, A; Roberts, C; Chauhan, A J; Thomas, M; Wilkinson, T M
Abstract : Introduction: In the UK, there is significant variation in respiratory care and outcomes. An integrated approach to the management of high-risk respiratory patients, incorporating specialist and primary care teams' expertise, is the basis for new integrated respiratory services designed to reduce this variation; however, this model needs evaluating. Methods: To evaluate an integrated service managing high-risk respiratory patients, electronic searches for patients with asthma and chronic obstructive pulmonary disease at risk of poor outcomes were performed in two general practitioner (GP) practices in a local service-development initiative. Patients were reviewed at joint clinics by primary and secondary care professionals. GPs also nominated patients for inclusion. Reviews were delivered to best standards of care including assessments of diagnosis, control, spirometry, self-management, education, medication, inhaler technique and smoking cessation support. Follow-up of routine clinical data collected at 9-months postclinic were compared with seasonally matched 9-months prior to integrated review. Results: 82 patients were identified, 55 attended. 13 (23.6%) had their primary diagnosis changed. In comparison with the seasonally adjusted baseline period, in the 9-month follow-up there was an increase in inhaled corticosteroid prescriptions of 23.3%, a reduction in short-acting β2 -agonist prescription of 33.3%, a reduction in acute respiratory exacerbations of 67.6%, in unscheduled GP surgery visits of 53.3% and acute respiratory hospital admissions reduced from 3 to 0. Only 4 patients (7.3%) required referral to secondary care. Health economic evaluation showed respiratory-related costs per patient reduced by £231.86. Conclusions: Patients with respiratory disease in this region at risk of suboptimal outcomes identified proactively and managed by an integrated team improved outcomes without the need for hospital referral.